Interpretation of Hadith in K-Pop Rejection Narratives within Digital Da‘wah on Social Media - Muyasaroh, Noor Wahidatul; Zulham Qudsi Farizal Alam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Background and Objectives: Popular culture has become a major arena for identity construction and value negotiation among youth worldwide. In Indonesia, the global rise of Korean Pop (K-Pop) has sparked tension with religious values, particularly as some Muslim preachers on social media reject K-Pop by citing specific hadith. This study investigates how hadith are represented in online preaching discourses against K-Pop and explores their role in shaping Muslim youth identity within the digital public sphere. Methods: A qualitative approach was employed using Fairclough’s critical discourse analysis. Data were collected from Instagram, YouTube, and TikTok content where hadith were invoked to criticize K-Pop. To deepen interpretation, the analysis combined Abou El-Fadl’s hermeneutics of moral reading with a socio-historical contextual approach, enabling the distinction between literal and contextual uses of hadith in digital da‘wah narratives. Main Findings: The findings demonstrate that hadith such as man tasyabbaha biqawmin fahuwa minhum and al-mar’ ma‘a man ahabba are often interpreted literally to portray K-Pop admiration as a threat to Islamic faith. However, moderate preachers adopt contextual readings that integrate ethical and historical considerations, offering more inclusive approaches to engaging youth. Contribution: This article contributes by filling a gap in existing literature that rarely foregrounds hadith as the core analytical object in the study of religion and popular culture. It provides a critical framework for understanding how sacred texts function in digital identity negotiation. Conclusion: The study concludes that contextual and ethically grounded interpretations of hadith are essential for developing communicative, relevant, and non-authoritarian da‘wah strategies, empowering Muslim youth to engage critically with global cultural flows while retaining strong religious identity.